(untitled) (Research, Society and Development, 2020)
Physical activity (PA) self-efficacy is the belief in one´s ability to perform this behavior at a given level of attainment, involving both a cognitive component and a power to choose. This integrative review aimed to identify studies concerning PA self-efficacy, whose conception stemmed both from Brazilian and foreign school physical education settings, in order to know their methodological framework and main findings. Studies, published from 2008 to 2018, were selected both in Portuguese and in English through the following databases: Google Scholar; BIREME/BVS; PUBMED; SCOPUS; and WEB OF SCIENCE, using the term self-efficacy along with the keywords Physical Education, health and teaching. 15 articles were summarized qualitatively, which were mainly written in English, being only two in Portuguese, and the domains of task self-efficacy, barrier self-efficacy and the Tripartite model emerged. These domains may explain gender physical activity behavioral change, self-efficacy variations after training, and relevant self-efficacy relational aspects that entail implications to school settings.